Stones : poems - Young, Kevin, 1970- (Alfred A. Knopf, 2021)
"A book of elegy, loss, and what binds us to life, by a towering poetic talent. "We sleep long, / if not sound," Young writes early on in this exquisite gathering of poems, "Till the end/ we sing / into the wind." In scenes and settings that circle family and the generations in the American South--one poem, "Kith," exploring that strange bedfellow of "kin"--the speaker and his young son wander among the stones of their ancestors. "Like heat he seeks them, / my son, thirsting / to learn those / he don't know / are his dead." Whether it's the Louisiana summer's fireflies in a mason jar (doomed by their collection), or his grandmother, Mama Annie, who latches the screen door when someone steps out for just a moment, all that comprises our flickering precarious joy, all that we want to protect, is lifted into the light in this moving book. Stones becomes an ode to Young's home places and his dear departed, and to what of them--of us--poetry can save"--